DYNAMIC PRICE AS BARGAINING RESULT FOR REVENUE MAXIMIZATION IN RETAIL - Deksnytė, Indrė; Lydeka, Zigmas; Pukelienė, Violeta (Ekonomika, 2014)
The application of dynamic price and its modeling was an authentic revolution for the traditional concept of price setting in business environment. The article reviews the essence and the main principles of dynamic price as a bargaining basis. Dynamic price fluctuation range in this paper is collated with the zone of agreement and introduced as an overlap between the maximum purchase price that the buyer is willing to pay and the minimum sell price that the seller is willing to accept. Therefore, the aim of this paper is to analyse the dynamic price as the bargaining basis, research problems, and to assess the dynamic price efficiency based on the dynamic price setting model experiment results. The experimental results suggest that dynamic price is a successful tacit bargaining practice.